Legislação de agroquímicos no Brasil: procedimentos para o registro de novos ingredientes ativos e produtos - Finazzi, José Gabriel Marialva (Universidade Federal de São Carlos, 2023)
The Brazilian legislation that provides for the experimentation, use, and application for registration of agrochemicals from Law n° 7,802 of 1989 and the decrees that regulate it, is a complex subject with several fundamentals and requires technical knowledge. The objective of this work was to present a review of agrochemical registration processes, encompassing studies of agronomic efficacy and feasibility, and studies of residues, and based on this, to prepare a didactic support material accessible to collaborate with knowledge on the subject. References were sought in publicly accessible material, in legislation, and on websites of the three competent agencies (ANVISA, MAPA, and IBAMA) in the application for registration of agrochemicals. We seek to clarify what agronomic efficacy and feasibility studies and residue studies are and how they work, pointing out what steps are required for an agrochemical to be registered as a commercial product. The support material was developed in a digital folder format because it is easier to transmit, it is a short and basic reading, in addition to being able to download and upload the file on electronic devices such as smartphones and notebooks, since it is public material. The Brazilian legislation on agrochemicals and how the procedures for registering them are carried out are relatively complex, and this material can serve as support for students of agricultural sciences, and a means of disseminating information on the subject.
Agrochemical legislation in Brazil: procedures for registering new active ingredients and products
Keywords: Assuntos regulatórios; Agrotóxico; Eficácia; Lei 7.802/89; Resíduo; Regulatory affairs; Agrochemical; Efficacy; Law 7.802/89; Residue; CIENCIAS AGRARIAS::AGRONOMIA::FITOSSANIDADE